The Reg protein family: potential new targets for the treatment of inflammatory bowel disease and colorectal cancer - Yao, Anqi; Huang, Cuilan; Wang, Xuyang; Zhou, Renmin; Hao, Wujuan (Frontiers in Gastroenterology, 2024)
Inflammatory bowel disease (IBD) comprises Crohn’s disease (CD) and ulcerative colitis (UC), both characterized by chronic intestinal inflammation and an elevated risk of colorectal cancer due to persistent inflammation. The Regenerating gene (Reg) family proteins exhibit properties that promote cell proliferation, inhibit apoptosis, reduce inflammation, combat microbial infections, and potentially modulate the immune system. There is increasing evidence of the potential function of the Reg family of proteins in the development of IBD and colorectal cancer, but the exact mechanism of action of the Reg family of proteins has not yet been fully clarified. In this paper, we reviewed the Reg protein family’s involvement in the development of IBD by regulating intestinal microbes and immunity to maintain intestinal homeostasis. We also explored its possible regulatory mechanisms and signaling pathways in the progression and treatment of colorectal cancer, which is expected to serve as a target and a new biomarker for the treatment of IBD and colorectal cancer in the future.